META ANALISIS: PENGARUH KOMPETENSI PROFESIONAL GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU - Apriliani, Azha; Yuniati, Suci; Rahmi, Depriwana; Kurniati, Annisah (FKIP Unirow Tuban, 2024)
The professional competence and work motivation possessed by teachers is something that plays an important role in their duties as teachers in schools. Teachers who have professional competence can be seen from the skills and knowledge they have in the field of teaching. Then the level of motivation can also increase the teacher's ability to carry out duties and responsibilities at school. With these conditions, it is hoped that it can improve teacher performance in teaching. The aim of this research is to analyze the influence of teacher professional competence and work motivation on teacher performance. In this research, the type of research used is a meta-analysis study. Data collection was carried out through literature study or literature review by analyzing 10 previous journals. Based on the research results, it shows that teacher professional competence and work motivation have a positive and significant influence on improving teacher performance. From the research results it can also be seen that teachers with professional competence and high work motivation are able to carry out their duties well and create an effective learning environment at school. Therefore, teacher professional competence and work motivation are important factors that can help improve teacher performance in schools.